Dry matter accumulation and nutrient cycling by soil cover plants in an intensive corn silage production system (Research, Society and Development, 2022)
This study aimed to evaluate dry matter accumulation and nutrient cycling by soil cover plants in an intensive corn silage production system. At the beginning of October, a study consisting of five soil cover plants, plus a control treatment (fallow area vegetation) was installed. The following cover plants were used: brachiaria brizantha, brachiaria ruziziensis, crotalaria juncea, jack bean and velvet bean. At the beginning of February of the year following sowing, we evaluated dry matter and nutrient accumulation in plant shoots. There was a significant effect at 0.1% of the cover plants on dry matter and nutrient accumulation. The average values ​​for dry matter accumulation in plant shoots were 19.88; 18.06; 16.38; 9.66; 8.96 and 4.26 t ha-1 for brachiaria brizantha, crotalaria juncea, brachiaria ruziziensis, jack bean, velvet bean and fallow area vegetation, respectively. The highest nitrogen accumulation was observed in crotalaria juncea (343 kg ha-1), followed by jack bean (269 kg ha-1). For brachiaria brizantha and ruziziensis, N accumulation of 247 and 216 kg ha-1 were found, respectively. Brachiaria brizantha had the highest accumulation of phosphorus and potassium, with average values ​​of 39 and 362 kg ha-1. In the fallow area vegetation, the accumulations of N, P and K were 42; 9.0 and 62 kg ha-1, respectively.